PENGARUH SUBSTITUSI TEPUNG JAGUNG KUNING (Zea mays L.) DAN PUREE WORTEL (Daucus carota L.) TERHADAP KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK MIE BASAH - Olivia, Dita Rizma; Damat, Damat; Manshur, Hanif Alamudin (Food Technology and Halal Science Journal, 2023)
Wet noodles are food products made from wheat flour that are not dried. Every year, the production and consumption of noodles in Indonesia is increasing. So, there is a need for food diversification in the raw material by utilizing local food ingredients such as corn flour. The use of carrot puree aims to increase the carotenoid content which acts as a good antioxidant for the body. This research was conducted using a simple Randomized Block Design (RBD) method. There were 6 treatments and 4 replication, P0 (100% wheat flour), P1 (50% wheat flour: 50% corn flour), P2 (50% wheat flour : 45% corn flour: 5% carrot puree), P3 (50% wheat flour: 40% corn flour: 10% carrot puree), P4 (50% wheat flour: 35% corn flour: 15% carrot puree), P5 (50% wheat flour: 30% corn flour: 20% carrot puree). The best wet noodles were obtained from treatment P5 (50% wheat flour: 30% corn flour: 20% carrot puree) with moisture content of 70.05%, ash content of 0.26%, fat content of 6.94%, protein content of 4.65%, carbohydrates content of 18.08% and carotenoids content of 3.02 mg/100g, brightness 63.5, yield 172.44%, organoleptic color 4.13 (attractive), aroma 3.63 (quite like), taste 3.80 (good), and texture 2.65 (not chewy).